Regional Dialogue on Infectious Diseases in South Asia - Babar, Summar Iqbal; Fatima, Sarosh (University of Wah Journal of Social Sciences, 2024)
A predictive health analytics company suggested that there is a 27.5% probability of a pandemic as lethal as COVID-19 occurring within the next ten years. The dramatic global spread of the coronavirus exposed the cracks in public healthcare systems and demonstrated the importance of regional cooperation in limiting the spread of infectious diseases. Heightening global connectivity has meant that the next epidemic or pandemic may only be a flight away. Due to climate change, the incidence of infectious diseases is increasing. The risk of outbreaks is especially high in regions strained by poverty and conflict, such as South Asia. Since diseases do not respect borders, they pose a grave danger to global health and human security, which makes cooperation between states and regions even more crucial. This article aims to explore a) how infectious diseases are an imminent threat to human security in South Asia, and b) how regional dialogue can dissipate the threats posed by emerging epidemics and pandemics in South Asia. Keywords: Health Security, Infectious diseases, South Asia, Non-Traditional Security, SAARC, Regional Dialogue.